Discrimination of cis-trans sex pheromone components in two sympatric Lepidopteran species. (June 2016) - Zhang, Sufang; Kong, Xiangbo; Ze, Sangzi; Wang, Hongbin; Lin, Aizhu; Liu, Fu; Zhang, Zhen
Abstract: Pheromone-binding proteins (PBPs) play an important role in the recognition of pheromones by insects. However, the abilities of these PBPs to discriminate pheromone components and recognize the isomers are unclear. Dendrolimus houi and Dendrolimus kikuchii are two sympatric coniferous pests whose pheromones have cis-trans isomers. We used these insect species to detect the precise recognition abilities of PBPs. The four PBPs examined showed male-biased antenna-intensive expression patterns, whereas PBP1 showed higher expression than PBP2 in the antenna. DhouPBP1 only bound to a minor interspecific pheromone component, whereas DhouPBP2 bound to all three intraspecific components and another minor interspecific component. DkikPBP1 and DkikPBP2 could recognize all three intraspecific components with affinities negatively correlated with their ratios, and they bound to interspecific pheromones with affinity that was positively correlated with the ratios. The four PBPs have different cis-trans isomer discrimination abilities, i.e., DhouPBP1 and DkikPBP1 could not discriminate the two cis-trans isomer pairs of pheromones from the two species, whereas DhouPBP2 could discriminate between both pairs, and DkikPBP2 could only discriminate one pair. Overall, PBPs from D. houi and D. kikuchii use different strategies to help the moths to discriminate the intra- and interspecific pheromone components. Our work will contribute to better understanding of the sex pheromone recognition mechanism in these two sister species of moths and provide insights into more effective management practices of these pest species. Graphical abstract: Highlights: Expression and function of PBPs from sympatric species are compared. Two PBPs from Dendrolimus houi exhibit different ligand-binding properties. Dendrolimus kikuchii PBPs bind inter- and intra-species pheromones with different affinity. PBP2 from D . houi can discriminate both two pair of cis-trans pheromone components from two species. PBP2 from D . kikuchii can discriminate cis-trans isomer E 5, Z 7-12:OAc and Z 5, E 7-12:OAc.